Mapping subtidal estuarine habitats with a remotely operated underwater vehicle (ROV). Issue 1 (2nd January 2020) - Wasserman, J; Claassens, L; Adams, JB
Abstract : Subtidal habitats have not yet been accounted for in habitat maps of South African estuaries. In this study, a novel method for mapping subtidal estuarine habitats, using a remotely operated underwater vehicle (ROV) piloted from a boat, was developed and tested in the Knysna Estuary. Video footage was recorded along 48 transects across the width of the estuary, and then reviewed to identify, classify and map habitats. Using the method developed in this study, 21 hours of footage was recorded over 15 days of sampling, and about 30 hours of post-processing was carried out to map an area exceeding 850 ha. This study has produced the first baseline dataset of subtidal habitats for a South African estuary. Additionally, the study revealed the previously unknown distribution of the invasive red seaweed Asparagopsis taxiformis, and the underestimation in previous studies of the estuary of area cover of eelgrass Zostera capensis by 130 ha.